Expediency and prospects of a vaccinal prevention of whooping cough without age restrictions - I. V. Mikheeva; T. S. Saltykova; M. A. Mikheeva (Журнал инфектологии, 2018)
The goal of study was the epidemiological substantiation of optimization measures of a vaccinal prevention of whooping cough in the Russian Federation. Materials and methods. The retrospective descriptive epidemiological research has been conducted by analysis of the official statistical data on the whooping cough case rate (form No. 2) in 2005–2017 in the Russian Federation, as well as the data about preventive whooping cough inoculations (forms No. 5, No. 6) in 2005–2017 and about epidemic outbreakes in 2017 (form No. 23-17). The assessment of an economic damage from whooping cough in 2005-2017 has been carried out. Results. The following adverse characteristics of a modern epidemiological situation on whooping cough in Russia are shown: long-term recurrence of epidemic process, tendency of rising of a case rate of children of 0-2 years; high percentage of children of preschool and school age among whooping cough cases; prevalence among the patients with whooping cough of the children who have been vaccinated against this infection previously, epidemic outbreakes in children’s collectives, the stability of a case rate of teenagers and adults with prevalence of the mild and the erased clinical forms of this infection. The risks due to weaknesses of the whooping cough vaccinal prevention are noted: the insufficient immunization coverage owing to falce contraindications and refusals of parents of vaccinations of children, noncompliance with terms and intervals between inoculations, lack of domestic vaccine for revaccination of children at the age of 5 years and older. Conclusion. It is necessary to introduce in the national vaccination schedule a preschool booster dose for children at the age of 6 and adolescents at 14 years with the combined reduced antigen content tetanus–diphtheria and acellular pertussis vaccines as well as the inoculations of this vaccine according to epidemiological indications to health workers, employees of educational institutions. A revaccination against whooping cough is recommended as “cocoon” for the persons contacting to not vaccinated child under 1 year of age.